WAQF MANAGEMENT IN INDONESIA: BETWEEN IDEALITY AND REALITY - Dunuraen, Mochamad Ae (Journal of Islamicate Studies, 2019)
Waqf is a public asset, which is a great hope for the community to be managed and utilized optimally both materially and spiritually. But waqf land always brings its own problems, especially in utilization that is always not optimal. Such as the eviction of buried land, mosques, and the re-occupation of land by heirs, the reality of life shows that there are still many cases of waqf disputes that arise in life, such as not registering waqf, waqf assets that are not maintained or neglected, switching waqf to third party in a way against the law, withdrawal of the land that has been represented, denial of waqf pledges by heirs, and many others. Management of waqf in accordance with the Islamic law, namely may sell waqf property, or exchange it, replace it, move the waqf property and use the proceeds of the sale to be used again for waqf interests. This ability, based on the reason that property waqf remains maslahah, in accordance with the purpose of waqf, or to get greater / better benefits for the benefit of humans in general.